2014
DOI: 10.1007/s00253-014-6120-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small molecule signaling factor that regulates the biosynthesis of the antifungal polycyclic tetramate macrolactam HSAF in Lysobacter enzymogenes

Abstract: Lysobacter species are emerging as new sources of antibiotics. The regulation of these antibiotics is not well understood. Here, we identified a small molecule metabolite (LeDSF3) that regulates the biosynthesis of the antifungal antibiotic HSAF (heat-stable antifungal factor), a polycyclic tetramate macrolactam with a structure and mode of action distinct from the existing antifungal drugs. LeDSF3 was isolated from the culture broth of L. enzymogenes, and its chemical structure was established by NMR and MS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 51 publications
5
70
0
Order By: Relevance
“…Why elevated c-di-GMP levels are inhibitory for HSAF production also remains unknown. Consistent with the notion that c-di-GMP signaling plays an important role in HSAF production is our earlier observation that HSAF production was lower in the rpfG mutant (13). The RpfG protein is an RR containing an HD-GYP domain, which is predicted, based on its similarity to RpfG from Xanthomonas (34), to have c-di-GMP phosphodiesterase activity.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Why elevated c-di-GMP levels are inhibitory for HSAF production also remains unknown. Consistent with the notion that c-di-GMP signaling plays an important role in HSAF production is our earlier observation that HSAF production was lower in the rpfG mutant (13). The RpfG protein is an RR containing an HD-GYP domain, which is predicted, based on its similarity to RpfG from Xanthomonas (34), to have c-di-GMP phosphodiesterase activity.…”
Section: Discussionsupporting
confidence: 63%
“…Two RR proteins (RpfG and PilG) were known to control HSAF levels, based on our earlier work (13,14). In the present work, we used the rpfG deletion mutant (ΔrpfG) as a control and confirmed that HSAF levels were significantly decreased in the mutant.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…This strategy is also relatively newly developed for marine microorganisms compared with soil studies. Recently, with Lysobacter , researchers identified a small molecule metabolite ( Le DSF3) that regulates the biosynthesis of HSAF [40]. The addition of Le DSF3 in L. enzymogenes cultures increases HSAF biosynthetic gene transcription and HSAF yield.…”
Section: Ahl Lactonasementioning
confidence: 99%